Characterization of major allergens of local mud crab (Scylla serrata) / Rosmilah Misnan … [et al.] - Misnan, Rosmilah; Abdul Rahman, Nurul Izzah; Mohd Yadzir, Zailatul Hani; Abdullah, Noormalin; Bakhtiar, Mohd Faizal; Murad, Shahnaz (Institute of Research Management and Innovation (IRMI), 2015)
Crab meat is widely consumed in several countries around the world. However, when consumed, crab meats are frequent cause of allergic reactions throughout the world. Scylla serrata is among the most common mud crab in Malaysia. In a previous study two major allergens of mud crab at 36 and 41 kDa was identified. Thus, the aim of this study is to further identify these major allergens by a proteomic approach. Protein extract was prepared and resolved by 2-dimensional electrophoresis (2-DE). Immunoblotting was then performed using reactive sera from patients with crab allergy. Major allergenic spots were then excised from the 2-DE gel and analysed by mass spectrometry. The 2-DE profile of the extract revealed approximately >100 protein spots between pH of 4.00 to 8.00. Mass spectrometry analysis has identified the 36 and 41 kDa proteins as tropomyosin and arginine kinase, respectively. Our findings indicated that tropomyosin and arginine kinase play a major role in allergic reaction to mud crab meat among local patients with crab meat allergy, and should be included in diagnostics and therapeutic strategies of this allergy.